Pengaruh Penggunaan Media Animasi Powtoon terhadap Motivasi dan Hasil Belajar IPA Peserta Didik Kelas VIII UPT SPF SMP Negeri 8 Makassar (Materi Usaha dan Pesawat Sederhana) - Ainun Rafiqha Nur; Sitti Rahma Yunus; Hasanuddin Hasanuddin (Universitas Negeri Makassar, 2026)
This study aims to determine 1) the level of motivation and learning outcomesoff class VIII SMPN 8 Makassar students after being taught using powtoon-based animation media in the experimental class 2) the level of motivation and learning outcomesoff class VIII SMPN 8 Makassar students after being taught conventional media in the control class 3) How high is the increase in motivation and learning outcomes of students in class VIII SMPN 8 Makassar after being taught using powtoon-based animation media in the ezperimental class 4) How high is the increase in motivation and learning outcomes of students in class VIII SMPN 8 Makassar after being taught using conventional media in the control class 5) Whether there is an effect of powtoo-based animation media on motivation and learning outcomes of science students in class VIII SMPN 8 Makassar. This type of research is quasi-experimental design research with a research design using Nonequivalent Control Group. The population of all VIII grade students at SMPN 8 Makassar in the 2023/2024 academic year consisted of 12 classes with a total of 396students. The sample was selected by purposive sampling with 2 classes, namely the experimental class (VIII-7) totaling 35 and the control class (VIII-9) totaling 37students. The research instrument was a questionnaire of motivationand a learning outcomes test.The results of the analysis showed that there was an effect of of powtoon-based animation media on learning motivation and science learning outcomes in class VIII students of SMPN 8 Makassar.